Economic Interactions: Trade And Investment Relations Between The Us And Central Asian Nations (Zien Journal of Social Sciences and Humanities, 2024)
Economic cooperation between the United States and Central Asian countries has become increasingly important in recent years due to mutual interests in trade and investment opportunities. With its rich natural resources and strategic geographic location, Central Asia has attracted US attention as a potential export market and investment hub. On the other hand, the United States offers advanced technologies and expertise sought by Central Asian countries seeking to diversify their economies and modernize their industries. These dynamic relations are mutually beneficial and have the potential to stimulate economic growth and prosperity, and promote stability and cooperation in the region. As we delve deeper into the complexities of these economic interactions, it is necessary to analyze the various factors shaping trade and investment relations between the United States and Central Asia